Uma nova espécie de Hylodes (Anura, Hylodidae) da Serra do Japi: descrição, modo reprodutivo e comunicação - Sá, Fábio Perin de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Hylodes species from Serra do Japi mountain range, included in the Hylodes lateristrigatus group, is a torrent frog endemic to this mountain range in the São Paulo state, Brazil; it exhibits territorial males and elaborated courtship behavior. It is morphologically similar to H. amnicola, H. ornatus, H. perere, and H. sazimai; however, distinguishable by its color pattern, advertisement call, and DNA sequences. Divided into two chapters, we present data on taxonomy, phylogenetic systematic, natural history, and conservation status, besides information on the reproductive mode and communication of this hylodid. In the chapter I we present the descriptions of the new species, including the description of its tadpoles. Moreover, in this chapter we provide, for the first time for a Hylodes species, details of the spawning, traits of the fertilized eggs, and the behavior of the female helping to conceal the underwater constructed chamber after oviposition. In the chapter II we study the communication of this species of torrent frog, revealing the most complex visual displays repertoire among amphibian anurans, including five new displays that we describe. Never before registered for frogs, we also describe the individualized use of the vocal sacs by the males, according to the receiver’s position, and the visual-tactile multimodal communication performed by females during the courtship. Finally, concluding the chapter II, a review on visual displays in Neotropical torrent frogs highlights the behavioral diversity currently known for the family Hylodidae. Our research evidences that it is important to conduct more studies comprising: (1) integrative taxonomy and phylogeny within the genus Hylodes, combining data on morphology, vocalizations, geographic distribution, and DNA sequences, thereby revealing potential cryptic species and, as a consequence, the true diversity of the genus; and (2) the visual communication in the genus Hylodes...

A espécie de Hylodes da Serra do Japi, que pertence ao grupo de Hylodes lateristrigatus, é uma rã-de-corredeira endêmica desta cadeia de montanhas no Estado de São Paulo, Brasil, e que apresenta machos territoriais e comportamento de corte elaborado. Apesar de ser morfologicamente similar à H. amnicola, H. ornatus, H. perere e H. sazimai, pode ser distinguida pelo seu padrão de coloração, suas características de canto de anúncio e por meio de análises moleculares. Dividido em dois capítulos, o presente estudo traz dados de taxonomia, sistemática filogenética, história natural e estado de conservação, além de informações referentes ao modo reprodutivo e à comunicação deste hilodídeo. No capítulo I são apresentadas a descrição da nova espécie assim como de seus girinos. Ainda, neste capítulo, são apresentados, pela primeira vez para uma espécie de Hylodes, detalhes da desova, características dos ovos fertilizados e o comportamento da fêmea auxiliando no fechamento da toca subaquática após a oviposição. O capítulo II aborda a comunicação desta rã-de-corredeira, sendo revelado o mais complexo repertório de sinais visuais entre os anfíbios anuros, incluindo cinco novos sinais visuais que são descritos. Nunca antes registrados para anuros, também são observados o uso individualizado dos sacos vocais pelos machos, de acordo com a posição do receptor, e a comunicação multimodal visual-tátil, realizada pelas fêmeas durante o ritual da corte. Por fim, fechando o capítulo II, uma revisão dos sinais visuais em rãs-de-corredeira neotropicais destaca a diversidade comportamental atualmente conhecida para a família Hylodidae. A presente dissertação de mestrado evidencia a importância da realização de mais estudos envolvendo: (1) taxonomia e filogenia integrativas com o gênero Hylodes unindo dados de morfologia, canto, distribuição geográfica e sequências de DNA, deste modo sendo reveladas...
Keywords: Anura; Anuro; Animais - Comunicação; Anfíbio; Rã; Morfologia (Animais); Japi, Serra do (SP)